Analysis of Load Testing on the Fresh Fruit Bunch Catching Component of the Electric Bunch Harvester (E-Bhar) Machine and its Impact on Fresh Fruit Bunch Quality - Miftah Ghiffari; Sam Herodian; Agus Sutejo (The University of Lampung, 2025)
This study aims to test the loading on the catcher components of the E-Bhar machine, as well as estimate the bruise index (BI) and free fatty acids (FFA) in the Fresh Fruit Bunches (FFB) caught. The loading test was conducted by dropping artificial FFB weighing 35 kg from a height of 1 m for 16 trials to analyze the deformation that occurred on the catcher components. Additionally, the BI was manually observed based on variations in the height of the FFB during harvesting. The results showed that an increase in the dropping height of the FFB caused an increase in potential force, which impacted the damage to the FFB. The potential force simulation results on the E-Bhar machine's catcher components ranged from 143.35 N to 2300.38 N, with BI values between 2.38 and 6.69. The maximum BI of 6.69 at a height of 10 m indicates damage approaching the critical value, thus threatening the quality of the FFB. The percentage of FFA ranged from 2.30% to 7.85%, exceeding the maximum limit of 5% set by the palm oil mill according to (SNI 01-2901-1992). These findings emphasize the advantage of using the catcher components in the E-Bhar machine to maintain good quality of the harvested FFB. Keywords: Bruise index, Catcher component, Deformation, Free fatty acids, Load testing.